Virtual museums using in the process of tourism disciplines studying - Dyshko, Olesia; Zubekhina, Tetiana; Belikova, Natalia; Denysenko, Nataliia; Zaichuk, Kateryna (My University, 2021)
The article substantiates the feasibility of virtual museums introducing into the process of studying tourism disciplines. The main advantages of implementing virtual museums such as accessibility (in particular for people with disabilities, low-income and imposed isolation), interactivity, informativeness, time limitless, safety, reliability and modernity have been identified. The use of virtual museums in different forms of pedagogical activity is described: work in and out of the class, advanced training and diagnostic tools. The results of a student survey, which confirmed the expediency of virtual excursions using in the educational process (it is interesting for students, increases the level of mastering professionally oriented knowledge and skills, contributes to the development of a sustainable in-depth interest in communicating with museum objects, the development of creative abilities, the formation of media competence) are presented. It is shown that virtual museums provide an opportunity to fill the learning process with new interesting content through the use of modern Internet technologies.
Keywords: Information and communications technology; Virtual reality; Virtual museum; Virtual tour